The Role Of Social Media Marketing Activities In Increasing Brand Loyalty - M. Haikal Sultana Abdullah; Aekram Faisal (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
The purpose of this study was to analyze the positive influence of social media marketing activities on brand loyalty both directly and through the mediating role of community engagement and brand engagement. The sample taken is with the criteria of individuals who have purchased fashion products on social media in the last 1 year. This study uses primary data obtained through questionnaires distributed to 211 respondents. Data were analyzed using the Structural Equation Model (SEM). The results of this study indicate that social media marketing activities do not have a direct (positive) influence on brand loyalty, but social media marketing activities have a positive influence on brand loyalty through the mediating role of community involvement and brand involvement.